Precision management influences productivity and nutrients availability in dryland cropping system - Mikha, Maysoon M.; Mankin, Kyle R.; Khan, Shahbaz B.; Barnard, David M. (Agronomy journal, 2024)
Precision management (PM) aims to reduce inputs while increasing land productivity and economical return and enhancing cropping system resiliency to climate change. This study evaluated how climate (precipitation) and management influenced yields and soil nutrients in a dryland agricultural system. We compared an “aspirational” (ASP) system (no‐till, 4‐year rotation of winter wheat [Triticum aestivum L.], corn [Zea mays L.], proso millet [Panicum miliaceum L.], and fallow/flex) to a traditional “business‐as‐usual” (BAU) system (reduced tillage, 2‐year rotation of winter wheat and fallow: W–F). Phases of each rotation were included yearly throughout the study period (2018–2022) with three replications. The ASP system incorporated PM by dividing each ASP field into three zones (high‐, medium‐, and low‐PM) according to prior yield and topography. Nitrogen was applied at high, medium, or low application rates within those zones. Under favorable precipitation, wheat, corn, and millet yields responded to PM treatments, with yields increasing proportional to N addition. Years with low in‐season precipitation had a significant reduction in wheat and corn yields (2020 and 2022) and complete millet yield failures (2020 and 2021). Low soil organic matter accumulation (0.1%–0.5%) and a reduction in soil macro‐ and micronutrient status suggested that soil nutrient additions are needed to prevent soil‐nutrient degradation. The ASP treatment added a third crop every 4 years and did so without significantly decreasing wheat yield following fallow. The ASP management shows promise as an alternative to BAU in the Great Plains dryland production region. Core Ideas Precision management could provide resilient cropping, maximize resources, and increase returns in dryland cropping. Dryland crop yields increased in response to in‐season precipitation and timing. Nitrogen responses were amplified/more notable in years with higher in‐season precipitation. Low soil organic matter accumulation and crop nutrient removal showed a potential to reduce soil nutrients status. Crop diversification and management could improve yields and mitigate climate variability of the Plains region.